1988
DOI: 10.1021/bi00418a003
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic estrogens: synthesis, interaction with lamb uterine estrogen receptor, and detection by infrared spectroscopy

Abstract: As an integral part of the development of a new technique using organometallic markers for the detection of hormone receptors by FT-IR spectroscopy, a series of estradiol derivatives labeled with Cr(CO)3 or Cr(CO)2CS fragments on the A ring has been synthesized. The stereochemistry of one of these steroids, alpha-[3-(dimethyl-tert-butylsiloxy)-17 beta-estradiol]dicarbonyl(thiocarbonyl)chromium(0), has been established by X-ray diffraction. The organochromium-labeled steroids are stable in aqueous methanol solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…Melikyan et al resolved the structure of a Co 2 (CO) 6 -complexed propargyl cation showing that the C ϩ atom is no longer equidistant from Co atoms. [24] The same behavior was observed in 3 ϩ , where the organometallic moiety shifts below the estradiol D ring, enabling a Mo-C (17) ϩ interaction to be established. [6] In the case of 3 ϩ this interaction is weaker than that reported for 3a ϩ , and interestingly, this difference has been attributed to the conformational constraints imposed by the bioligand.…”
Section: %mentioning
confidence: 66%
See 2 more Smart Citations
“…Melikyan et al resolved the structure of a Co 2 (CO) 6 -complexed propargyl cation showing that the C ϩ atom is no longer equidistant from Co atoms. [24] The same behavior was observed in 3 ϩ , where the organometallic moiety shifts below the estradiol D ring, enabling a Mo-C (17) ϩ interaction to be established. [6] In the case of 3 ϩ this interaction is weaker than that reported for 3a ϩ , and interestingly, this difference has been attributed to the conformational constraints imposed by the bioligand.…”
Section: %mentioning
confidence: 66%
“…The quantification of the [ 3 H]estradiol specifically bound to the ER was then performed by protamine sulfate precipitation as previously described. [17] The residual radioactivity on the precipitate is related to the remaining estrogen binding activity: the higher the radioactivity, the lower the receptor inhibition (RI% ϭ 0 for estradiol itself). [18] Carbenium ions can be generated in presence of strong acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C) as previously described 26 was used as a source of cytosolic ERα. For purified ERβ, 10 µl of the solution containing 3500 pmol/mL were added to 16 ml of buffer B (10% glycerol, 50 mM bis-Tris-propane pH = 9, 400 mM KCl, 2 mM DTT, 1 mM EDTA, 0.1% BSA) in a silanized flask.…”
Section: Determination Of the Rba Of The Compounds For Erα (From Cytomentioning
confidence: 99%
“…These molecules, in which the M2Cz tetrahedral moiety is situated on the a-face of the steroid, are known to bind to various steroidal receptor sites (7,8). Moreover, it has been demonstrated that one can take advantage of the intense metal carbonyl infrared stretching absorptions to assay the receptor sites without any of the inconveniences associated with radio-labels (9,10).…”
Section: Introductionmentioning
confidence: 99%